2015
DOI: 10.1007/s11746-015-2679-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Method for Quantitation of Soybean Lectin in Commercial Varieties

Abstract: for a capture phase and the biotinylated version (Gal-NAc-PAA-Biotin) for detection. Based upon the validation data, the ELLA method can precisely and accurately determine soybean lectin levels in soybean seed. The validated ELLA method was used to quantify SBA in nine commercial soybean varieties introduced between 1972 and 2008 and demonstrated that the natural variability of SBA is subject to the effects of genotype and environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Lectins (agglutinins) are a group of protein‐binding carbohydrates which are found in several plants, especially legume seeds. In SBM, lectins are tetrameric protein constituted of 30 kDa subunits with binding specificity towards galactose and N‐acetylgalactosamine (Breeze et al., 2015). It is reported that lectins have a potentially interfere with physiological status (metabolism) of poultry and swine (Pusztai, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Lectins (agglutinins) are a group of protein‐binding carbohydrates which are found in several plants, especially legume seeds. In SBM, lectins are tetrameric protein constituted of 30 kDa subunits with binding specificity towards galactose and N‐acetylgalactosamine (Breeze et al., 2015). It is reported that lectins have a potentially interfere with physiological status (metabolism) of poultry and swine (Pusztai, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Overall these included furfural, sodium, selenium, and vitamin C for maize and crude fiber for soybean. In addition, soybean lectins were also omitted because the analytical method used in most cases (hemagglutination assay) is known to be sensitive to specific lab conditions 16 compromising data comparability across field trial studies. The complete list of the compositional end-points included in our investigation is provided in Table 1.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Key nutrients and anti-nutrients were analyzed from harvested maize grain and harvested soybean seed. Validated analytical methods, consistent with those described in refs , , or , were used to assess analyte levels. Resulting data were combined by entry across all replicates and locations within a study, and combined site mean values for each component were calculated.…”
Section: Methodsmentioning
confidence: 99%